OF ASHTRAYS AND INCOMMENSURABILITY: REFLECTIONS ON HERBERT BUTTERFIELD AND THE WHIG INTERPRETATION OF HISTORY. - McClay, Wilfred M. (Fides et historia, 2012)
The article discusses the 1931 book "The Whig Interpretation of History," by Herbert Butterfield. Topics include an April 1972 incident at the Institute for Advanced Study in Princeton, New Jersey involving filmmaker Errol Morris and philosopher Thomas Kuhn, the biographies "Herbert Butterfield: Historian As Dissenter," by C. T. McIntyre, and "The Life and Thought of Herbert Butterfield: History, Science, and God," by Michael Bentley, and the views of historian Lord John Emerich Edward Dalberg Acton on historiography in relation to Butterfield's views.